A review on bio-electrochemical systems (BESs) for the syngas and value added biochemicals production. (June 2017) - Kumar, Gopalakrishnan; Saratale, Rijuta Ganesh; Kadier, Abudukeremu; Sivagurunathan, Periyasamy; Zhen, Guangyin; Kim, Sang-Hyoun; Saratale, Ganesh Dattatraya
Abstract: Bio-electrochemical systems (BESs) are the microbial systems which are employed to produce electricity directly from organic wastes along with some valuable chemicals production such as medium chain fatty acids; acetate, butyrate and alcohols. In this review, recent updates about value-added chemicals production concomitantly with the production of gaseous fuels like hydrogen and methane which are considered as cleaner for the environment have been addressed. Additionally, the bottlenecks associated with the conversion rates, lower yields and other aspects have been mentioned. In spite of its infant stage development, this would be the future trend of energy, biochemicals and electricity production in greener and cleaner pathway with the win-win situation of organic waste remediation. Henceforth, this review intends to summarise and foster the progress made in the BESs and discusses its challenges and outlook on future research advances. Highlights: Bio-electrochemical systems (BESs), its mechanism and their types are reviewed. BESs for production of cleaner gaseous fuel like H2 and CH4 are reviewed. BESs for of electrical energy and biochemicals production are reviewed. Bottlenecks associated with conversion rate and yields are discussed. Discussed future challenges to develop research interest in BESs.